NASKAH ARAB DAN LONTARA DI SULAWESI SELATAN, BARAT, DAN TENGGARA - Muhaeminah Muhaeminah; mardan mardan (Balai Arkeologi Kalimantan Selatan, 2009)
Old manuscript discovered in South, West, and Southeast Sulawesi are usually written in Buginese letter (lontara) and Arabic Serang letter in local language. Manuscript written in Arabic using local language were found in Wolio each indicating the same content concerning Islamic wisdom similar to the Quran and also comprises the hadist, fiqh, and players. The manuscript are in degrading forms, incomplete and do not bear date, however, water marks are present indicating the chronology. Navertheless, there are old manuscript are well kept in the regional museum and archive office.